Produção de microbolhas utilizando a indução de ar atmosférico para melhorias no processo de flotação por ar dissolvido (FAD) - Henauth, Rosangela Cristine da Silva (2015)
The continuous expansion of the hydrocarbon processing industry and the extensive use of petroleum-related products has increased the threat of pollution by this type of product in the environment. In the industries, in general, there is a great demand for good quality water and much of the volume of water will be eliminated for receiving bodies with a high load of organic matter and solids. Thus the wastewater generated in all industrial processes needs to have a specific treatment. Some physical-chemical processes are widely requested, including the dissolved air flotation (DAF), where the production of microbubbles is essential for an effective treatment of the contaminated effluent. In this research an innovative technique was proposed for producing microbubbles for the treatment of oily water. The new technique induces a flow of air in the suction of a centrifugal pump, depending on the negative pressure existing at this point in the installation line. A central composite rotational design was used to determine the efficiency of the method. Within the working conditions, independent variables were identified by the ratio between the air flow and water (X1) and the pressure in the pump discharge (X2) line. When tested in a dissolved air flotation prototype (DAF), the technique provided a separation efficiency of 97 % water/oil. According to the results obtained, the above method proved to be advantageous compared to to the conventional process of saturation of the effluent treated with compressed air, by reducing the number of equipment and the energy costs.